Performance trajectories for competitive swimmers: The role of coach interpersonal behaviors and athlete motivation - Rocchi, M. A.; Guertin, C.; Pelletier, L. G.; Sweet, S. N. (Motivation Science, 2019)
This study investigated the longitudinal trajectories of athletes` competitive performance results, as well as the motivational predictors of the emerging trajectories. In 2010, a group of 413 competitive swimmers were asked to provide background characteristics (age, gender, years of experience) and complete self-determination theory-based measures of their coaches` interpersonal behaviors and sport motivation. The athletes` performances were then followed for seven swimming seasons (2011-2017) and their top score from each season was used to track their trajectories over time. The data were analyzed using latent class growth analysis to determine the best-fitting model of performance trajectories, while controlling for athletes` background characteristics. Athletes` perceptions of coaches` behaviors and their motivation were explored as predictors using a multinomial logistic regression. The analyses revealed 5 latent classes: Early Dropout (23%) Delayed Dropout (40%), Stable (9%), Improvement (18%), and High-Performance (11%). Multinomial logistic regression analysis indicated that, in 2010, members of the Improvement and High-Performance classes reported higher perceived autonomy support (ORs >1.58, CI95s > 1.00) and relatedness support (ORs >1.58, CI95s > 1.00) than the Early Dropout and Delayed Dropout groups. The Stable, Improvement, and High-Performance groups reported less non-self-determined motivation in 2010 than the Early Dropout and Delayed Dropout Groups (ORs < .43, CI95s < 1.00). These results support that perceptions of coaches` interpersonal behaviors and athletes` motivation predict performance trajectories among swimmers over time.